Chemoprofiling of Andrographis Paniculata (Kalmegh) for its Andrographolide Content in Madhya Pradesh, India - SHWETA MISHRA; S.K. TIWARI; ARUN KAKKAR; A.K.PANDEY (International Journal of Pharma and Bio Sciences, 2010)
Andrographis paniculata (Burm.f.) Nees (Acanthaceae) is a medicinal plant traditionally used for the treatment of cold, fever, laryngitis and several infectious diseases ranging from malaria to dysentery and diarrhoea. The plant is widely used in Ayurvedic and Homeopathic systems of medicines. The medicinal value of this plant is due to the presence of active ingredients viz andrographolide and neoandrographolide which are derivatives of diterpenoids. The content of these active ingredients in plant varies with in plant parts and with the geographical distribution. In order to study the variation in andrographolide content, plant material was collected from 15 districts of Madhya Pradesh and evaluated through a simple, quick and accurate HPLC method using C-18 ODS-2 column. The chemoprofiling study showed significant variations in the concentration of active ingredients in the leaves as well as in whole plant. The study also revealed that andrographolide content was maximum in leaves of the accession collected from Seoni(1.82%) followed by Chhindwara (1.48%).